Identification and analysis of internal promoters in Caenorhabditis elegans operons - Huang, Peiming; Pleasance, Erin D.; Maydan, Jason S.; Hunt-Newbury, Rebecca; O’Neil, Nigel J.; Mah, Allan; Baillie, David L.; Marra, Marco A.; Moerman, Donald G.; Jones, Steven J.M. (Genome Research, 2007)
The current Caenorhabditis elegans genomic annotation has many genes organized in operons. Using directionally stitched promoter∷GFP methodology, we have conducted the largest survey to date on the regulatory regions of annotated C. elegans operons and identified 65, over 25% of those studied, with internal promoters. We have termed these operons “hybrid operons.” GFP expression patterns driven from internal promoters differ in tissue specificity from expression of operon promoters, and serial analysis of gene expression data reveals that there is a lack of expression correlation between genes in many hybrid operons. The average length of intergenic regions with putative promoter activity in hybrid operons is larger than previous estimates for operons as a whole. Genes with internal promoters are more commonly involved in gene duplications and have a significantly lower incidence of alternative splicing than genes without internal promoters, although we have observed almost all trans-splicing patterns in these two distinct groups. Finally, internal promoter constructs are able to rescue lethal knockout phenotypes, demonstrating their necessity in gene regulation and survival. Our work suggests that hybrid operons are common in the C. elegans genome and that internal promoters influence not only gene organization and expression but also operon evolution.
10.1101/gr.6824707